A Benzothiazole Derivative (5g) Induces DNA Damage And Potent G2/M Arrest In Cancer Cells - Hegde, Mahesh (Sci Rep, 2017)
Chemically synthesized small molecules play important role in anticancer therapy. Several chemical compounds have been reported to damage the DNA, either directly or indirectly slowing down the cancer cell progression by causing a cell cycle arrest. Direct or indirect reactive oxygen species formation causes DNA damage leading to cell cycle arrest and subsequent cell death. Therefore, identification of chemically synthesized compounds with anticancer potential is important. Here we investigate the effect of benzothiazole derivative (5g) for its ability to inhibit cell proliferation in different cancer models. Interestingly, 5g interfered with cell proliferation in both, cell lines and tumor cells leading to significant G2/M arrest. 5g treatment resulted in elevated levels of ROS and subsequently, DNA double-strand breaks (DSBs) explaining observed G2/M arrest. Consistently, we observed deregulation of many cell cycle associated proteins such as CDK1, BCL2 and their phosphorylated form, CyclinB1, CDC25c etc. Besides, 5g treatment led to decreased levels of mitochondrial membrane potential and activation of apoptosis. Interestingly, 5g administration inhibited tumor growth in mice without significant side effects. Thus, our study identifies 5g as a potent biochemical inhibitor to induce G2/M phase arrest of the cell cycle, and demonstrates its anticancer properties both ex vivo and in vivo.